Unpacking gender mainstreaming: a critical discourse analysis of agricultural and rural development policy in Myanmar and Nepal - Cheong, Dawn D.; Bock, Bettina; Roep, Dirk (Agriculture and human values, 2024)
Conventional gender analysis of development policy does not adequately explain the slow progress towards gender equality. Our research analyses the gender discourses embedded in agricultural and rural development policies in Myanmar and Nepal. We find that both countries focus on increasing women’s participation in development activities as a core gender equality policy objective. This creates a binary categorisation of participating versus non-participating women and identifies women as responsible for improving their position. At the same time, gender (in)equality is defined exclusively as a women’s concern. Such discourses, as constitutive practices, produce specific knowledge about rural women and new subjectivities that prescribe and govern them solely as subjects of development. Our research suggests that such a limited discursive practice invisiblises gendered power relations and structural and institutional issues, ultimately slowing progress towards gender equality. We demonstrate the importance of studying policy as discourse, beyond the effectiveness of policies or mainstreaming tools, and call for empirical evidence on the impact of these discourses on women’s subjectivities and lived experiences.